Decay of Resonaces in Strong Magnetic Field. (July 2015) - Filip, Peter
Abstract: We suggest that decay properties (branching ratios) of hadronic resonances may become modified in strong external magnetic field. The behavior of K ±*, K 0* vector mesons as well as Λ * (1520) and Ξ 0* baryonic states is considered in static fields 10 13 -10 15 T. In particular, n = 0 Landau level energy increase of charged particles in the external magnetic field, and the interaction of hadron magnetic moments with the field is taken into account. We suggest that enhanced yield of dileptons and photons from ρ 0 (770) mesons may occur if strong decay channel ρ 0 → π + π - is significantly suppressed. CP – violating π + π - decays of pseudoscalar η c and η (547) mesons in the magnetic field are discussed, and superpositions of quarkonium states ηc, b and χc, b ( nP ) with Ψ( nS ), ϒ( nS ) mesons in the external field are considered.